PEMIKIRAN PSIKOLOGIS AL-FARABI (Renungan Awal Menuju Psikologi Islam) - Soleh, A. Khudori (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2008)
Potency of human being soul, according to al-Farabi, consisted of the grow energy (vegetative), momentum (animal), illusive energy (imagine), natural existence energy (ratio) and feel energy. We obtain our knowledge by externals senses related to momentum, and internal senses existing in illusive energy, also the intellect existing in natural existence energy.However, this intellect is unlike ratio. It resides above ratio, because ratio works and thinks only pursuant to data of senses, whereas intellect works pursuant to radiation from "above" (divine being), so that there's no mistaking. Intellect consists of 4 levels: potential intellect, actual intellect, acquirement intellect, and active intellect. In the process of knowledge, active intellect is source of human being knowledge obtained after we powered potential and actual intellect.Keywords: energy of soul and intellect.